Understanding health system responsiveness to public feedback at the sub-national level: Insights from Kilifi County, Kenya. - Nancy Kagwanja; Lucy Gilson; Benjamin Tsofa; Jill Olivier; Hassan Leli; Sassy Molyneux (PLOS Global Public Health)
Responsiveness is one of four health system goals alongside health outcomes, equity in financing and efficiency. Many studies examining responsiveness report a composite satisfaction index or proportions of patients describing satisfaction with dimensions of responsiveness. Consequently, responsiveness is predominantly based on collation of service users' feedback and could be termed service responsiveness. We conceptualise system responsiveness more broadly, as how the health system more widely responds to concerns or needs of the public. In this paper we share a system responsiveness framework to reflect this wider conceptualisation and illustrate how we used this framework combined with Aragon's insights on organisational capacity, to explore system responsiveness practices at sub-national level in Kenya. Drawing on interviews and group discussions we specifically consider how two governance structures -Health Facility Committees (HFCs) and Sub-County Health Management Teams (SCHMTs)- found in many Low-and-Middle-Income (LMIC) health systems receive, process, and respond to public feedback. HFCs are formal structures with community representation linked to a health facility to support community participation in service provision and health outcomes. SCHMTs comprise middle-level managers with oversight over primary health care facilities and are commonly known as district health management teams in other LMICs. There were multiple feedback mechanisms through which the health system could receive public feedback, but these mechanisms had limited functionality, often worked in isolation, and inadequately represented vulnerable groups. Our analysis also revealed the organisational capacity gaps that constrain health system responsiveness. These gaps ranged from inadequate funding and staffing of feedback mechanisms (hardware), through absence of clear procedures and guidelines (tangible software), to norms, actor relationships and power dynamics (intangible software elements). Our findings are relevant to similar low-and-middle-income contexts and draw attention to the importance of integrating multiple mechanisms and forms of feedback, alongside considering system capacities and their interactions, in strengthening health system responsiveness.